KEPRIBADIAN TOKOH DIKTA DALAM NOVEL DIKTA DAN HUKUM KARYA DHIA’AN FARAH - Harbeng Masni; Indah Kurnia Sari (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this research is to describe a personality in the novel Dikta dan Hukum by Dhia'an Farah. This research includes a qualitative descriptive research described in the findings in the form of expressions contained in the novel Dikta dan Hukum by Dhia'an Farah. The data is in the form of expressions contained in the novel Dikta dan Hukum by Dhia'an Farah. The type of research used in this study is a descriptive type of research. The approach used is qualitative. Qualitative is a research approach that the author will use in processing data. The results of this research shows the use of 9 expressions of personality in the novel Dikta dan Hukum by Dhia'an Farah. For the most dominant aspect of personality, namely the id personality found as many as 32 expressions, and the least found is the ego personality, which amounts to 12 expressions. While the superego personality occured in 18 expressions.